Terrorist Myth Construction Using Bits Arrangement on Acting in the Movie Long Road to Heaven - Ambar Setiawati, Sudibyo JS.; Banowo, Emilianshah; Bayangkari Doeana, Bintang; Im, Cik; Aru Wiratno, Tri (Universitas Pasundan, 2025)
The Bali Bombers claim to be mujahideen, while the public considers them terrorists. Whose assumption is correct? The identity of a character is not 'who he is' but 'how he is'. This research answers that question through bits arrangement. Bit is the smallest unit of action that contains an objective. Within a bit, there are thoughts, moods, and ways of expression. The identity of a bit is symbolized by active verbs, such as: scolding, advising, loving, being jealous, and so on. As for arrangement, it is the concept of operationalizing acting. If the identity of a terrorist or mujahid is to be attributed to the Bali Bombers, then the action is orchestrated to meet the specified characteristic traits. The effort to identify the essential aspects and operationalize bits arrangement is pursued through Stanislavski's Realistic Acting Theory. The object of this research is a film titled Long Road To Heaven. This research produces cinematic findings: the artistic mythologization of the terrorist character in the Bali Bombers.